Agroholdings as the Subjects of the Economy Globalization – the Example of Ukraine - Kiforenko, Oksana (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The objective of the paper is to define the factors that contribute to the development of the agricultural sector of Ukraine’s economy, to analyze the places Ukraine takes in the world rankings of agricultural production and export and the share of the agricultural and food industry products in the total exports volume of Ukraine, to define the main markets for Ukrainian agricultural products, to identify the role agroholdings play in the functioning of the Ukrainian agricultural sector, to define the main factors that contributed to the emergence and development of the agroholdings in Ukraine and to make the list of the most profitable agroholdings in Ukraine. The following general scientific and specific economic methods were used in the paper: the statistical analysis methods, the method of ratings, the information – computer methods, the critical analysis method, the monographic method, the case study method and the graphical method.